Monetary Policy Preferences of the EMU and the UK. (22nd July 2015) - Arestis, Philip; Karoglou, Michail; Mouratidis, Kostas
Abstract : We estimate the central bank policy preferences for the European Monetary Union and for the UK. In doing so, we extend the theoretical framework suggested by Cecchetti et al . ( T he M anchester S chool, Vol. 70 (2002), pp. 596–618), by assuming that policy preferences change across different regimes. Our empirical results suggest that the weight that policy makers put on inflation is typically profound. Furthermore, it appears that volatility shifts of the economic disturbances are the main factor, which generates variation in policy preferences.